TINDAK TUTUR EKSPRESIF PADA EPISODE “BERANI BONGKAR DUGAAN DALANG TAMBANG ILEGAL” PODCAST CURHAT BANG DENNY SUMARGO - Linda Yustati, Emilia; Susilawati, Lis; Zahrotul Lutfiyah, Luly (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines how individuals express themselves through the disclosure of previously suppressed emotions in response to specific situations. The research was conducted on the Curhat Bang Denny Sumargo podcast channel, which featured Serly Tjoanda, the Governor of North Maluku, in an episode titled